ANALYSIS OF THE INFLUENCE OF SNAKEFRUIT SKIN ASH ON THE COMPRESSIVE STRENGTH OF K-175 CONCRETE - Nova Syafitri Siregar; Motlan Motlan (Universitas Negeri Medan, 2026)
Research has been carried out on K-175 concrete with a mixture of snakefruit bark ash with the aim of determining the effect of snakefruit bark ash on the mechanical properties of K-175 concrete. The test object used was a cube measuring 15 cm x 15 cm x 15 cm with standardization SNI-7394-2008 with quality K-175 with a cement ratio of 1: 2.3: 3.1 with FAS 0.6. The mechanical properties testing carried out was compressive strength testing and determining the crystal structure and filler phases of the concrete after soaking for 28 days and drying for 24 hours. Based on the research results with a mixture of snake fruit ash (0%, 0.5%, 1%, 2%, 4%) the average compressive strength test results were 18.11 Mpa, 17.21 MPa, 17.02 MPa, 20, respectively. 23 MPa, and 16.80 Mpa. Where the test is carried out after the concrete is 28 days old. From the results of the compressive strength test, the concrete experienced an insignificant decrease in compressive strength with each addition of snakefruit bark ash, but the compressive strength increased with the percentage of snakefruit bark ash (2%). The maximum compressive strength result with a mixture of snakefruit bark ash was 20.23 Mpa. Based on the test results and X-Ray Diffraction analysis results, it shows that the concrete samples containing silica are mostly amorphous, it can be seen in the graphic image that there is only a very small amount of X-ray diffraction which has sharp and angular peaks, this shows that the crystalline content is getting smaller thus most of the contained in the sample is amorphous.